Communication Challenges in a Multi-Campus University System in Ghana: The Case of University for Development Studies (UDS) - Dinye, Amatus; Boon, Emmanuel K.; Asante, Job (Ghana Journal of Higher Education Management, 2024)
The paper focuses on the three dispersed campuses of University for Development Studies (UDS). It analyses the communication system of the University and the associated challenges. The qualitative research design and case study approach guided the investigation and analysis. A structured interview guide facilitated the collection of information from 35 purposively selected key officers (managers) engaged in the day-to-day administration of UDS’s three campuses. In addition, 45 randomly sampled supporting staff (administrators) and students from the three campuses participated in a Focal Group Discussion (FGD). Thus, 80 members of the University participated in the study. The paper revealed that the current communication system used by administrators of the University is not up to date and inefficient. For efficient management of UDS, the deployment of modern communication technologies is highly recommended. This will enable the campus administrators to communicate in real-time. UDS needs to develop a communication policy to facilitate efficient communication.